Calnexin Depletion by Endoplasmic Reticulum Stress During Cholestasis Inhibits the Na+‐Taurocholate Cotransporting Polypeptide. Issue 12 (23rd October 2018) - Robin, Marion J.D.; Appelman, Monique D.; Vos, Harmjan R.; van Es, Robert M.; Paton, James C.; Paton, Adrienne W.; Burgering, Boudewijn; Fickert, Peter; Heijmans, Jarom; van de Graaf, Stan F.J.
Abstract : Cholestasis‐induced accumulation of bile acids in the liver leads to farnesoid X receptor (FXR)‐mediated transcriptional down‐regulation of the bile acid importer Na + ‐taurocholate cotransporting protein (NTCP) and to induction of endoplasmic reticulum (ER) stress. However, whether ER stress affects bile acid uptake is largely unknown. Here, we investigated the role of ER stress on the regulation and function of the bile acid transporter NTCP. ER stress was induced using thapsigargin or subtilase cytotoxin in human osteosarcoma (U2OS) and human hepatocellular carcinoma (HepG2) cells stably expressing NTCP. Cellular bile acid uptake was determined using radiolabeled taurocholate (TCA). NTCP plasma membrane expression was determined by cell surface biotinylation. Mice received a single injection of thapsigargin, and effects of ER stress on NTCP messenger RNA (mRNA) and protein were measured by reverse‐transcription polymerase chain reaction (RT‐PCR) and western blot analysis. Effects of cholestasis on NTCP and ER stress were assessed in response to 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine (DDC) feeding or bile duct ligation in FXR –/– mice after 7 or 3 days, respectively. Novel NTCP‐interacting proteins were identified by mass spectrometry (MS), interaction verified, and assessed by co‐immunoprecipitation and TCA uptake for functional relevance in relation to ER stress. ER stress induction strongly reduced NTCP protein expression, plasma membrane abundance, and NTCP‐mediated bile acid uptake. This was not controlled by FXR or through a single unfolded protein response (UPR) pathway but mainly depended on the interaction of NTCP with calnexin, an ER chaperone. In mice, expression of both NTCP and calnexin was reduced by thapsigargin or cholestasis‐induced ER stress. Calnexin down‐regulation in vitro recapitulated the effect of ER stress on NTCP. Conclusion : ER stress‐induced down‐regulation of calnexin provides an additional mechanism to dampen NTCP‐mediated bile acid uptake and protect hepatocytes against bile acid overload during cholestasis. Abstract : ER‐stress induction strongly reduces NTCP protein expression, plasma membrane abundance and NTCP‐mediated bile acid uptake. This is not controlled via a single UPR‐pathway but mainly depends on the interaction of NTCP with calnexin, an ER chaperone. In mice, expression of both Ntcp and calnexin is reduced by thapsigargin or cholestasis‐induced ER‐stress. Calnexin downregulation in vitro recapitulates the effect of ER‐stress on NTCP. In concluion, ER stress‐induced downregulation of calnexin provides an additional mechanism to dampen NTCP‐mediated bile acid uptake and protect hepatocytes against bile acid overload during cholestasis.